(untitled) (Journal of Nepalese Business Studies, 2018)
Tax knowledge is the major factor contributing to raise revenue for the country. The objective of this study is to investigate the level of tax knowledge of university teachers. Questionnaire has been administered including five point likert scale classifying different items of tax knowledge from 193 university teachers in Pokhara employing convenience sampling method. The results suggestes that tax knowledge has a significant impact, even though the level of tax knowledge varies significantly among respondents. The result indicates that more attention should be given to deliver tax related information in order to increase tax knowledge among university teachers. Relating to tax knowledge, results reveals that there is no significant difference on the basis of marital status, type of college and gender. The results of this study can inform policymakers on the extent to which tax knowledge is important in a self assessment system and in what ways it can affect compliance. The Journal of Nepalese Business Studies Vol. X No. 1 December 2017, page: 69-77